PRESENTATION OF FINANCIAL REPORTS BASED ON SAK EMKM AT PT SOLOMON INDO GLOBAL - Ana Nur Janah; Arief Nurdiannova Qurochman (Jurnal Ekonomi, 2023)
This research aimed to examine the financial statements of PT Solomon Indo Global and assess their compliance with SAK EMKM, the Financial Accounting System for Micro, Small, and Medium-sized Entities. Using a qualitative approach, primary data were collected through company interviews, supplemented by supporting data from daily cash-in and cash-out records to the financial statements. The findings revealed that the company's financial statement recordings were in line with SAK EMKM. However, only three out of the five required financial reports for MSMEs were available, namely profit and loss reports, reports on changes in capital, and statements of cash flows. The company's cash flow statement met global criteria for cash reports, yet the identification of inflow and outflow transactions lacked clarity. The company solely used a bank account (account name) for each transaction. Nevertheless, the final cash flow statement result matched the bank's cash result on the balance sheet. Aside from the weaknesses in presenting some cash flow statements, two types of financial reports were missing - a report on changes in capital and notes on financial statements. In conclusion, PT Solomon Indo Global's financial statements were generally compliant with SAK EMKM, but certain improvements are needed, including providing the missing financial reports and enhancing the clarity of cash flow transactions.